Corrigendum to “Emerging business models in local energy markets: A systematic review of peer-to-peer, community self-consumption, and transactive energy models” [Renew Sustain Energy Rev 179 (2023) 113273](S1364032123001296)(10.1016/j.rser.2023.113273) - Schwidtal, J. M. (2023)
Schwidtal, J. M., Piccini, P., Troncia, M., Chitchyan, R., Montakhabi, M., Francis, C., Gorbatcheva, A., Capper, T., Mustafa, M. A., Andoni, M., Robu, V., Bahloul, M., Scott, I. J., Mbavarira, T., España, J. M., & Kiesling, L. (2023). Corrigendum to “Emerging business models in local energy markets: A systematic review of peer-to-peer, community self-consumption, and transactive energy models” [Renew Sustain Energy Rev 179 (2023) 113273](S1364032123001296)(10.1016/j.rser.2023.113273). Renewable and Sustainable Energy Reviews, 185(October), [113523]. https://doi.org/10.1016/j.rser.2023.113523 ---Funding Information: Ian Scott was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS. Funding Information: Merlinda Andoni received funding from the EPSRC DecarbonISation PAThways for Cooling and Heating (DISPATCH) project (grant number EP/V042955/1 ) and the InnovateUK Responsive Flexibility (ReFLEX) project [ref: 104780]. Funding Information: Valentin Robu was supported by the project “TESTBED2: Testing and Evaluating Sophisticated information and communication Technologies for enaBling scalablE smart griD Deployment”, funded by the European Union Horizon2020 Marie Skłodowska-Curie Actions ( MSCA ) [Grant agreement number: 872172 ].